Demystifying the database: the state's crafting of Cape Town's housing allocation tool and its technologies - Greyling, Saskia (Department of Environmental and Geographical Science, 2022)
The City of Cape Town's integrated housing database is used to manage the allocation of state housing across the city. It is a technical intervention in a contested and politicised context. On the surface, it appears to be an effective state tool that determines eligibility for housing assistance, and subsequently, the implementation of fair housing allocation practices. This veneer of technicality, however, conceals the complex state work involved in the production, maintenance, and use of the database. In the context of South Africa's transition from apartheid to democratic modes of governance, this research examines the database to engage with the state's work in producing tools for legitimate decision-making. As a state tool, the database and its functioning has been largely rendered invisible, either dismissed because of the opacity of its functioning, or positioned as a political myth, a smokescreen that conceals the state's inability to deliver on its housing promises. However, a technopolitical lens challenges researchers to pay attention to the form, function and development of state tools; nuances that are too often overlooked. In this research I therefore examine the housing database as a legitimate state tool for fair housing allocations. Using archival material, I explore the making of the database. Based predominantly on interview material with key informants, I investigate the production of the data held within the database. I consider, through policy and document analysis, the use of the database and its data in the actual practice of housing allocation decision-making. In sum, the research tracks the ideological, political, bureaucratic, and technological shifts that have shaped the database over three decades of housing allocation reform. Through this analysis of the development, form, and function of the database, I substantiate the ways in which the database works as a mode of governance, crafted by the state, that builds and sustains housing allocation decision-making. Demystifying the database as a state tool highlights its gradations, textures and contradictions. Its analysis makes visible the state craft that is key to its development, form, and function – what shapes the state's housing allocation decision-making. This analysis opens up the South African housing crisis beyond the impasse where citizen need exceeds the state's capacity to supply houses, and shifts the narrative away from an ambivalent, unwilling or uncaring state, to one that makes visible and describes the state's craft on housing allocation decision-making.